Analisis Ketepatan Tata Cara Penulisan Karya Ilmiah Dalam Penyusunan Proposal PTK Dalam Kajian Sistematis Struktur Dan Standar Penulisan - Isna Maulida; Firmatul Ayniyah; Raihan Alimul Fata; Marcella Dwi Nur Rohma; Imron Fauzi (Yayasan Al-Afif, 2026)
Scientific papers are an essential component of academic activities as they function as a means of communicating ideas, research findings, and the advancement of knowledge in a structured and accountable manner. This study aims to examine the implementation of scientific writing conventions in the preparation of Classroom Action Research (CAR) proposals, particularly concerning their organization, structure, and writing standards. A qualitative approach with a library research method was employed in this study. Data sources included books, accredited national journals, and official guidelines related to scientific writing. The data were analyzed descriptively through data collection, review, categorization, and interpretation. The results reveal that CAR proposals prepared with appropriate organization, proper academic language, and adherence to academic ethics tend to demonstrate higher quality. Therefore, these findings are expected to provide practical guidance for students and researchers in developing CAR proposals that comply with established academic standards.